Elaboration of a mechanism for sustainable enterprise development in innovation ecosystems - Tatyana Tolstykh; Leyla Ayvarovna Gamidullaeva; Nadezhda Shmeleva (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper highlights a sustainability and self-organization perspective of the innovation ecosystems. Such issues as under what conditions self-organization takes place and what mechanisms form an innovation ecosystem in a sustainable way are underexplored in the academic literature. To ensure self-development of actors in the ecosystem, a self-adjustment mechanism is needed that allows implementation of sustainability principles. This article proposes a practical tool for assessing an actor in an ecosystem using the method of analytic hierarchy process (AHP), developed by T. Saaty. It allows for operationalizing the processes of self-organization in the ecosystem without an external intervention and addresses the main implications for sustainable development of innovation industrial ecosystems. The authors illustrate their assumptions with an empirical case study of the industrial ecosystem "Technologies for Improving the Quality of Life" (Moscow, Russia). The propositions arising from this analysis provide information to help academics, policymakers, government, and individual enterprises with a more adequate understanding of the practical mechanisms and tools that help trigger self-organization and sustainable development of the innovation ecosystems.
Keywords: 650; innovation ecosystem; industrial ecosystem; sustainability; self-organization; analytic hierarchy process (AHP); cross-validation